Acipenser ruthenus Linnaeus 1758 ... - Jouladeh-Roudbar, Arash; Ghanavi, Hamid Reza; Doadrio, Ignacio (Zenodo, 2020)
Acipenser ruthenus Linnaeus, 1758 – Native (Fig. 22) Acipenser ruthenus Linnaeus [C.] 1758: 237; Type locality:? Danube River. Holotype: NRM 96. based on several sources this specimen may be the holotype, see Kottelat (1997). Acipenser koster Gmelin [J. F.] 1789: 1486; Type locality: Caspian Sea. Acipenser pygmaeus Pallas [P. S.] 1814: 102; Type locality: Major seas and rivers of Europe. No types known. Acipenser kostera Fitzinger [L. J. F. J.] 1832: 340; Type locality: Danube River, Vienna, Austria. Neotype: BMNH 1898.4.11.26. Acipenser marsiglii Brandt [J. F.] in Brandt & Ratzeburg 1833: 352; Type locality: Danube River or Ob River. Holotype:? ZIN 11825. Acipenser kamensis Lovetsky [A.] 1834: 262; Type locality: Kama River, Russia. No types known. Acipenser aleutensis Fitzinger [L. J. F. J.] in Fitzinger & Heckel 1836: 285; Type locality: Canaga Island, Aleutian Islands, Alaska, U.S.A. [in error]. No types known. Acipenser gmelini Fitzinger [L. J. F. J.] in Fitzinger & Heckel 1836: 276; Type ... : Published as part of Jouladeh-Roudbar, Arash, Ghanavi, Hamid Reza & Doadrio, Ignacio, 2020, Fig. 4 in Fig. 4 in Fig. 3 in Fig. 21. Sesarmops mora n in Paralbunea dayriti, pp. 1-303 in Zoological Studies 59 (21) on pages 16-17, DOI: 10.6620/ZS.2020.59-21, http://zenodo.org/record/12822787 ...